Enhancement of flux pinning properties in nanosized MgO added Bi-2212 superconductor through neutron irradiation - Mohiju Z.A.; Hamid N.A.; Abdullah Y. (American Institute of Physics Inc., 2023)
For superconducting material to maintain high critical current density, Jc in any applications, effective flux pinning centers are needed. The addition of small size MgO particles in bulk Bi2Sr2CaCu2O8 (Bi-2212) superconductor has been proven to enhance the effective flux pinning centers in the superconducting material by creating a desired microstructure with appropriate defects. To further enhance the pinning properties, radiation is one of the convenient ways to improve the microstructure of the material that has correlation with basic properties of superconductors. Neutron irradiation is one of the niche techniques that can be used to perform the task. Defects with larger radius have dimension comparable to the coherence length of the material and thus improved its superconducting properties. In this paper, a small amount of nanosized MgO particles was used to create defects in the Bi-2212 superconducting material. The Bi- 2212/MgO compounds were heat treated, followed by partial melting and slow cooling. Part of the samples was subjected to neutron irradiation using the TRIGA-MARK-II research reactor at the Malaysian Nuclear Agency. Characterization of non-irradiated and irradiated samples was performed via the temperature dependence on electrical resistance measurements, X-ray Diffraction Patterns (XRD), and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray (EDX) analysis. From the analysis, there was changed in the critical current density and transition temperature of samples subjected to neutron irradiation due to formation of point defects in the microstructure. Higher critical current density indicates better flux pinning properties in the Bi-2212/MgO compounds.